1156 CANGRELOR IN PATIENTS WITH CORONARY ARTERY DISEASE PRE-TREATED WITH TICAGRELOR: THE SWITCHING ANTIPLATELET (SWAP)-5 STUDY. (15th December 2022) - Giordano, Salvatore; Franchi, Francesco; Ortega-paz, Luis; Rollini, Fabiana; Galli, Mattia; Been, Latonya; Ghanem, Ghussan; Shalhoub, Awss; Ossi, Tiffany; Rivas, Andrea; Zhou, Xuan; Pineda, Andres M; et al.
Abstract: Objectives: To rule out a drug-drug interaction (DDI) among cangrelor-treated patients who have been pre-treated with ticagrelor. Background: There are no studies specifically designed to rule out a DDI when cangrelor is used among patients who have been pre-treated with ticagrelor. Methods: In this prospective, randomized, double-blind, placebo-controlled, cross-over, pharmacokinetic (PK) and pharmacodynamic (PD) study, patients with coronary artery disease (n = 20) were pre-treated with a 180-mg ticagrelor loading dose (LD) and after 1 hour randomized to placebo or cangrelor (bolus and infusion for 2 hours). Patients crossed over after 1-4 weeks of washout. PK analysis included ticagrelor plasma levels and its active metabolite. PD assessments included: VerifyNow P2Y12 reaction units (PRU), light transmittance aggregometry vasodilatorstimulated phosphoprotein, and Total Thrombus-Formation Analysis System. PK/PD assessments were performed at 7-time points. Results: Compared to placebo, adding cangrelor to patients pre-treated with ticagrelor resulted in a significant reduction in PRU at 30 min and 1 hour after starting infusion. At 2 hours after stopping cangrelor/placebo infusion, PRU was low and similar in both groups (16.9 vs. 12.6; mean difference: 4.3; 95%CI: -28.6; 37.3), meeting the non-inferiority primary endpoint (predefined non-inferiority margin 45 PRU). Consistent findings were shown with all PD assays. PK tracked PD findings with no differences between groups in plasma levels of ticagrelor and its metabolite. Conclusions: Compared with placebo, the use of cangrelor in patients pre-treated with ticagrelor results in enhanced platelet inhibition with no differences in PK/PD profiles after discontinuation of drug infusion indicating the absence of a DDI.